Perancangan Sistem Informasi Manajemen Asosiasi dengan Metode Waterfall dan RBAC di Majelis Diktilitbang Muhammadiyah - Rosidin, Muhamad; H., Muhammad Haedar Z.; Sulistyo, Wicaksono Yuli (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The Higher Education, Research, and Development Council of Muhammadiyah oversees various associations with diverse activities, yet data management is still conducted manually, making it inefficient and prone to errors. This study aims to develop a web-based association management information system using the Laravel and Filament frameworks. The Waterfall method is applied in the development process, which includes requirements analysis, system design, implementation, testing, and maintenance. The system implements Role-Based Access Control (RBAC) to manage user access rights according to their roles. Key features include data management for associations, members, activity types, and activity history. Black Box testing results show that the system functions according to specifications, and usability evaluation indicates that the system is user-friendly. The developed system significantly improves efficiency, accuracy, and structured management of association activities. In conclusion, this information system provides an effective solution for association management and can be adopted by similar organizations to enhance operational efficiency.